Effect of Pomegranate barks solution (Punica granatum L) On some Pathogenic bacteria in vitro - Hassan, W. A. (The Iraqi Journal of Veterinary Medicine, 2004)
Powder of pomegranate barks (Punica granatum L) was prepared. Different concentration of watery pomegranate solution contain, 5, 10, 20, and 40 mg / ml were prepared Six types of pathogenic bacteria were used. Suspension was made from those bacteria and each type of bacteria contain (10x1 - 10x2) / ml. Those bacteria include Escherichia coli, Salmonella, Staphylococcus, Streptococcus, Klebsiella and Corynebacterium The affect of the plant solution of pomegranate was tested on petri - dishes containing Trypticase Soya agar by diffuse agar method. Equal amount of each type of the tested bacteria was mixed with the varying concentration of plant of pomegranate barks solution. All petri – dishes of the tested bacteria with the pomegranate barks powder were incubated at 37 c for 1-2 days. The result showed that the pomegranate barks solution of 40 mg / ml had the strongest inhibiting zone on all tested types of bacteria, while solution of 20 mg/ml. showed weak inhibiting zone. But the lower concentration showed no inhibiting zone for any of the tested bacteria.